90 Minutes in Heaven - Yoakam, Dwight; Batson, Bobby; Meek, Hudson; 1981-; Christensen, Hayden; 1983-; Bosworth, Kate; 1950-; Piper, Don; Polish, Michael; Universal Studios Home Entertainment (Firm); Giving Films (Universal City, CA, 2015)
Based on a true account and New York Times best-selling book comes the feature film adaption. Don Piper experienced love, joy and life like he2d never known during the 90 minutes he was declared dead after a traffic accident. But when he finally wakes in the hospital, Heavens bliss was replaced by excruciating pain and emotional turmoil. With the support of his family and community, Don clings to his faith and fights to recover the life hes lost.
Keywords: Drama; Christianity; Religious aspects; Death; Drama; Christianity; Future life; Drama; Christianity; Heaven; Christianity; Religious aspects; Near-death experiences; Drama; Video recordings for the hearing impaired; Film adaptations; Feature films; Fiction films; Christian films